AKTIVITAS FOSFOLIPASE-A2 SEKRETORIS PLASMA TROMBOSITOPENIA DEMAM BERDARAH DENGUE - Endang Retnowati K; Wiyanda Hidayati S; Liana . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Infected macrophages by dengue virus will produce phospholipase-A2 (PLA2) enzyme, that can promote arachidonic acidmetabolism that produce inflammatory mediators, causing endhothelial damage and severe plasma leakage. Capillary endothelialdamage can cause platelet adhesion and aggregation, so that many platelets will be consumed. The role of sPLA2 (secretoryphospholipase-A2), which is a part of PLA2 in dengue and thrombocytopenia up to now has not been widely studied. The objective ofthe study is to analyze the association between the activity of plasma secretory phospholipase-A2 and the degree of thrombocytopeniain DHF adult patients. the study is carried out by a cross sectional, observational analytical study on 45 hospitalized adult patientssuffering dengue hemorrhagic fever in the Tropical Infection Ward, Department of Internal Medicine, Dr. Soetomo Hospital Surabaya,which has been conducted from February–December 2009. The diagnosis of Dengue Haemorrhagic Fever (DHF) was based on the1997 World Health Organization (WHO) criteria, that minimally had one positive serology marker of dengue. Venous blood wastaken from the patient for examining the activity of secretory phospholipase-A2 by correlated enzyme assay method, and plateletcount using automated hematology analyzer. The results of the secretory phospholipase-A2 activity and degree of thrombocytopeniawere analyzed by Pearson correlation test to determine the correlation between the two variables. In this study so far was foundthat the secretory phospholipase-A2 activity in DHF patients was 36.9–195.6 unit/mL (mean 97.49 unit/mL, SD 30.06 unit/mL).The mean of secretory phospholipase-A2 activity was increased according to the degree of thrombocytopenia severity. The mean ofsecretory phospholipase-A2 activities were 91.65 unit/mL, 98.94 unit/mL, and 110.47 unit/mL. The degree of thrombocytopeniawas divided into mild, moderate, and severe. Most of the patients showed mild thrombocytopenia. The sPLA2 activity in this studywas increased in DHF patients with second day of fever, and then decreased at the third and forth day of fever, and increased inDBD patients suffering fifth day of fever. The statistical analyzes show a non significant correlation between secretory phospholipaseA2 activity and degree of thrombocytopenia (p = 0.579). This result may be caused by several factors which influencing thethrombocytopenia in DHF, such as bone marrow suppression, dengue viral serotype, influence of cytosolic phospholipase-A2 (cPLA2)activity, and other proinflammatory cytokines which in this study could not be controlled. Statistical analyzes show a significantcorrelation between sPLA2 activity and the day of fever (p = 0.04). Further studies should have to be carried out in order to knowthe pattern of sPLA2 activity in DHF grade I, II, III, and IV, and to know the influence of other proinflammatory cytokines and viralserotypes in sPLA2 activities.